Combined effects of oat bran consumption and brisk walking exercise on immune functions in 40 to 50 years old women - Abidin, Muhammad Amrun Haziq (Universiti Sains Malaysia, 2016)
Moderate physical activity and adequate nutritional intake arebelieved can enhance immune function of an individual. To date, little is known about combination effects of exercise and oat bran consumption on immune functions in 40 to 50 years old women. Therefore, the present study was carried out. This study was carried out to examine the beneficial effects of combined brisk walking exercise and oat bran consumption on immune functions in 40 to 50 years old women. Thirty three 40 to 50 years old women were recruited and assigned into three groups, with eleven participants per group (n= 1 1): sedentary without oat bran consumption control (C), oat bran consumption alone (Ob) and combined oat bran consumption and brisk walking exercise (ObEx) groups. The brisk walking exercise was performed by the participants three times per week for six weeks. Oat bran powder was consumed by the participants with two sachets per day (18g of oat bran powder containing 3.6 grams of P-glucan) diluted with plain water, 7 days per week for 6 weeks in Ob and ObEx groups. Participants in ObEx consumed oat bran drink one hour before performing the exercise. Immediately before and after six weeks of the experimental period, participants’ anthropometric parameters were measured. Blood samples were taken before and after experimental period in order to measure total white blood cells, neutrophils, basophils, eosinophils, monocytes, total lymphocytes, total T lymphocytes (CD3+), T helper cells (CD4~), T cytotoxic cells (CD8+) and natural killer cells (CD16+) for determining the level of immune functions Participants’ body weight decreased significantly (p<0.05) at post test in Ob and ObEx group. There were significant (p<0.05) increases in eosinophil and neutrophil counts in post test compared to pre test in Ob group. There were also significant (p<0.05) decreases in values of T cytotoxic (CDS^ and natural killer cells (CD16+) in post test compared to pre test in ObEx groups. For white blood cells, monocytes, basophils, total lymphocytes, total T lymphocytes (CD3+) and T helper cells (CD4+), no significant changes were observed in post test compared to pre test among all groups. Six weeks of oat bran consumption alone elicited the beneficial effect on immune functions. Thus, consumption of oat bran alone may have the potential to be recommended for increasing immune functions in 40 to 50 years old women. Nevertheless, future study with different exercise intensities and longer duration are proposed to be carried out to investigate the effects of combined oat bran consumption and brisk walking exercise on immune functions in this population.